2015
DOI: 10.1016/j.curtheres.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daikenchuto on Abdominal Bloating Accompanied by Chronic Constipation: A Prospective, Single-Center Randomized Open Trial

Abstract: BackgroundDaikenchuto (DKT), a traditional Japanese herbal medicine, is widely used for treatment of gastrointestinal disorders. We evaluated the efficacy and safety of DKT for abdominal bloating in patients with chronic constipation.ObjectiveTo evaluate the efficacy and safety of DKT for the treatment of abdominal bloating.MethodsAfter discontinuing as-needed use of laxatives, 10 patients received oral DKT for 14 days (15 g/d). To evaluate small intestinal bacteria overgrowth (SIBO), a glucose breath test was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 13 publications
2
20
0
2
Order By: Relevance
“…Furthermore, its pharmacology, including safety and pharmacokinetics is established. The long safety record of TU-100 use for post-operative ileus and constipation (12, 14, 55, 56) together with our preclinical findings of chemopreventive efficacy of TU-100, suggest that this is a potentially promising agent to test in a clinical trial to prevent colonic polyp recurrence.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, its pharmacology, including safety and pharmacokinetics is established. The long safety record of TU-100 use for post-operative ileus and constipation (12, 14, 55, 56) together with our preclinical findings of chemopreventive efficacy of TU-100, suggest that this is a potentially promising agent to test in a clinical trial to prevent colonic polyp recurrence.…”
Section: Discussionmentioning
confidence: 93%
“…DKT has been reported to be effective against constipation in specific cases, such as Parkinson's disease, pregnant women, and stroke patients [ 19 21 ]. Yuki et al reported that DKT significantly improves constipation and indigestion in chronic constipation based on the Gastrointestinal Symptom Rating Scale [ 15 ]. Thus, it can be suggested that DKT significantly improves constipation and self-evaluated indigestion.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying these effects of DKT is not found in western medicine, enabling a holistic approach [ 14 ]. According to a previous report, DKT improved the self-assessment scale for constipation [ 15 ]. However, the examination was conducted only in 10 cases, and stool frequency did not increase.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we showed the possible effectiveness of concomitant herbal medicines. Daikenchuto is an herbal medicine that is effective for bloating in patients with CC, probably via action on the gut microbiota [ 11 , 12 ]. Rikkunshito is a ghrelin enhancer and is effective against upper gastrointestinal symptoms [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%